Implantable biomimetic microelectronic systems design. - Wentai Liu
In this article, design examples will be presented for a biomimetic microelectronic system for a retinal prosthesis that electrically stimulates the retinal neurons. The system replaces the functionality of vision in blind patients affected by retinitis pigmentosa and age-related macular degeneration. The components and signal processing needed for a cortical prosthesis are described. Integration of all the components of a wireless biomimetic microelectronic system, such as input signal conditioning, power telemetry, data telemetry, stimulation amplifier and control circuitry (microstimulator), and a neural recording and processing device, into a single chip or a package is a tremendous challenge, requiring innovative approaches at both circuit and system levels and consideration of the multiple trade-offs between size, power consumption, flexibility in functionality, and reliability of the microelectronics. The chips described in this paper are prototypes for testing their implemented functionalities. The die sizes do not reflect the actual size of the implant. When the microelectronics are finally integrated, the circuits will be optimized to minimize the area. The use of submicron CMOS technology will also help reduce the die area. It should be noted that the biocompatible package encapsulating the electronics will increase the implant size.
Keywords: Age-related macular degeneration; Biocompatible package; Blind patients; Control circuitry; Cortical prosthesis; Data telemetry; Electrical stimulation; Implantable biomimetic microelectronic systems design; Input signal conditioning; Microstimulator; Neural processing device; Neural recording device; Power telemetry; Retinal neurons; Retinal prosthesis; Retinitis pigmentosa; Signal processing; Single chip; Stimulation amplifier; Submicron CMOS technology; Vision; Wireless biomimetic microelectronic system